2001
DOI: 10.1038/sj.dmfr.4600610
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders: relationship between joint pain and effusion and nitric oxide concentration in the joint fluid.

Abstract: Painful joints are more likely to demonstrate contrast enhancement of joint effusion. Nitric oxide concentration in TMJ fluid is closely associated with inflammatory changes and painful TM joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
2
30
0
4
Order By: Relevance
“…2 Further, MRI reveals other conditions that could be associated with TMJ pain, such as bone marrow abnormalities 3 and joint effusion. 4 An imaging examination, as well as other diagnostic tests, can be justified only if the results of the examination contain information that leads to a more accurate diagnosis and thus influences the choice of treatment and the prognosis. The diagnostic method should not only be accurate in distinguishing between diseased and healthy individuals but also be reliable in its observer independence, as it is well known that the diagnostic outcome is influenced by variations in the performance of different observers.…”
Section: Introductionmentioning
confidence: 99%
“…2 Further, MRI reveals other conditions that could be associated with TMJ pain, such as bone marrow abnormalities 3 and joint effusion. 4 An imaging examination, as well as other diagnostic tests, can be justified only if the results of the examination contain information that leads to a more accurate diagnosis and thus influences the choice of treatment and the prognosis. The diagnostic method should not only be accurate in distinguishing between diseased and healthy individuals but also be reliable in its observer independence, as it is well known that the diagnostic outcome is influenced by variations in the performance of different observers.…”
Section: Introductionmentioning
confidence: 99%
“…One such chronic inflammatory syndrome includes TMD in which NOS and NO have been identified both in the synovial fluid [Takahashi et al, 1996[Takahashi et al, , 1999Suenaga et al, 2001] and in the synovial tissues of individuals experiencing pain and tissue pathology [Homma et al, 2001]. In this regard, the histopathology associated with TMD, particularly in individuals who have had surgical intervention and disc replacement, includes mononuclear cell infiltrates and the presence of multinucleated giant cells ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a significant correlation has been reported between severity of pain and levels of TNF· in synovial fluid of TMD [Shafer et al, 1994], and TNF· levels were higher in TMD with bony changes [Fu et al, 1995]. Since TNF· is one of multiple inducers of nitric oxide [Bogdan, 2001], it was anticipated and demonstrated that NO was elevated in affected synovial tissues of TMD, as in other arthritides [Homma et al, 2001], and might correlate with joint pain [Suenaga et al, 2001] and/or degenerative changes [Takahashi et al, 1996[Takahashi et al, , 1999. Disruption of the inflammatory cascade with nonsteroidal anti-inflammatory agents (NSAIDs), cyclooxygenase 2 (COX2)-selective inhibitors, and/or surgical intervention, which may include repair, removal or replacement of the intra-articular disc have had limited success [Ta et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Effusionen zeigen sich zumeist im lateralen Gelenkbereich und im anterosuperioren Gelenkraum mit einer prozentualen Häufigkeit im Patientenkollektiv um 20%, wobei aber auch Angaben von 13 und 88% vorliegen [4,12,41 69,95,97]. Inwiefern Effusionszeichen Ausdruck eines entzündlichen und/oder degenerativ-arthrotischen Vorgangs im Gelenkbinnenraum oder lediglich einer Ansammlung (vermehrter) Gelenkflüssigkeit sind, ist derzeit noch nicht abschließend geklärt [28,69,99,108].…”
Section: Effusionunclassified
“…bilateralen schmerzhaften Diskusverlagerungen ohne Reposition und klinisch assoziierter Hypomobilität verglich, stützen die Annahme, dass eine deutliche Ausprä-gung der Gelenkeffusion im Kernspintomogramm mit Synovitis verbunden ist [94]. Die zusätzliche intravenöse Applikation von Kontrastmittel (Gadolinium-DTPA) und der anschließende kernspintomographische Vergleich vor und nach Bolusinjektion sollen schmerzhafte Gelenke deutlich besser von nicht schmerzhaften Gelenken diskriminieren [97].…”
Section: Effusionunclassified